2021
DOI: 10.1042/bsr20203944
|View full text |Cite
|
Sign up to set email alerts
|

An epithelial–mesenchymal transition-related long noncoding RNA signature correlates with the prognosis and progression in patients with bladder cancer

Abstract: Bladder cancer is a common malignant tumour worldwide. Epithelial–mesenchymal transition (EMT)-related biomarkers can be used for early diagnosis and prognosis of cancer patients. To explore, accurate prediction models are essential to the diagnosis and treatment for bladder cancer. In the present study, an EMT-related long noncoding RNA (lncRNA) model was developed to predict the prognosis of patients with bladder cancer. Firstly, the EMT-related lncRNAs were identified by Pearson correlation analysis, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
(27 reference statements)
2
41
0
Order By: Relevance
“…Six FRlncRNAs were included in the relevant clinical prediction models, which showed a good prediction effect for patients with BC. Tong et al found that AL049840.3, AL031775.1, and USP30-AS1 may predict the prognosis and progression of patients with BC as an epithelial-mesenchymal transition- (EMT-) related lncRNAs [ 29 ]. Wang et al found that OCIAD1-AS1 and AL354919.2 may predict the prognosis and progression of patients with BC as immune-related lncRNAs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six FRlncRNAs were included in the relevant clinical prediction models, which showed a good prediction effect for patients with BC. Tong et al found that AL049840.3, AL031775.1, and USP30-AS1 may predict the prognosis and progression of patients with BC as an epithelial-mesenchymal transition- (EMT-) related lncRNAs [ 29 ]. Wang et al found that OCIAD1-AS1 and AL354919.2 may predict the prognosis and progression of patients with BC as immune-related lncRNAs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these LncRNAs, U62317.3 which targeted GZMB and IRF1 was reported to exert and important effect on tongue cancer through the miR let7 family 33 . LINC02446 which targeted CASP1, CASP4, GZMB, IL18, IRF1, AIM2, NLRP1, GZMA was found to inhibit the metastasis of bladder cancer cells 34 and melanoma 35 , and act as a prognostic signature in bladder cancer 36 . HSD11B1-AS1 which targeted NLRP1 and NLRP3 was reported to participate in corticoid metabolism and relevant physiological function 37 .…”
Section: Discussionmentioning
confidence: 99%
“…LINC02446 is associated with prognosis (53) and EMT activation (54) in bladder cancer. Similarly, USP30-AS1 is associated with prognosis in bladder cancer (54). This lncRNA was also associated with autophagy in ovarian cancer (55), and was related to immune response in cervical cancer (56) and glioblastoma (57).…”
Section: Discussionmentioning
confidence: 99%